Emotional experience in music fosters 18‐month‐olds' emotion–action understanding: a training study. Issue 6 (9th September 2015) - Siu, Tik Sze Carrey; Cheung, Him
Abstract: We examine whether emotional experiences induced via music‐making promote infants' use of emotional cues to predict others' action. Fifteen‐month‐olds were randomly assigned to participate in interactive emotion training either with or without musical engagement for three months. Both groups were then re‐tested with two violation‐of‐expectation paradigms respectively assessing their sensitivity to some expressive features in music and understanding of the link between emotion and behaviour in simple action sequences. The infants who had participated in music, but not those who had not, were surprised by music–face inconsistent displays and were able to interpret an agent's action as guided by her expressed emotion. The findings suggest a privileged role of musical experience in prompting infants to form emotional representations, which support their understanding of the association between affective states and action. Abstract : Training 15‐month‐olds to recognize emotions via interactive musical activities not only enhances their appreciation of musical expressiveness, but also promotes their affective interpretation of behaviour.